Smart Monitoring: Proteksi Transmisi dari Drop dan Over Voltage - Agus Kiswantono (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2025)
In this research, current and voltage measurements were conducted to monitor and protect the electrical distribution system in real-time. The voltage was measured using a ZMPT101B sensor with a range of ±250V. An Arduino microcontroller was used to read the voltage values and calculate the average voltage over a specific period. This voltage measurement is crucial for detecting disturbances such as overvoltage and undervoltage. For instance, if the voltage exceeds 220V, the system detects the overvoltage condition and activates a relay to disconnect the electrical supply, thus protecting electrical equipment from damage due to excess voltage. Additionally, an ACS712 sensor was used to measure the current with a range of ±5A. The microcontroller calculates the average current value and detects any current surges exceeding the threshold of 5A. If the measured current exceeds this threshold, the system automatically activates the relay to disconnect the electrical supply, preventing damage to equipment or fires due to excessive current. With this protection system, it is expected to enhance the security and reliability of electrical distribution, as well as minimize the risk of disturbances that could damage equipment and improve the operational efficiency of the distribution system. The implementation of continuous current and voltage measurements also provides more accurate and responsive monitoring of the system's condition, facilitating prompt decision-making in a short time. This system is expected to be applied across various sectors to improve protection and efficiency in electrical energy distribution.